Pseudomonas aeruginosa pyocyanin and 1-hydroxyphenazine inhibit fungal growth. Issue 5 (1st May 1999) - Kerr, J R; Taylor, G W; Rutman, A; Høiby, N; Cole, P J; Wilson, R
Abstract : AIM: To examine strains of Pseudomonas aeruginosa for specific antifungal factors. METHODS: Two clinical strains of P aeruginosa with strong in vitro inhibition (by cross streak assay) of Candida albicans and Aspergillus fumigatus were examined. Both strains were isolated from sputum--one from a patient with cystic fibrosis and one from a patient with bronchiectasis. Bacterial extracts were fractionated by high performance liquid chromatography and examined by ultraviolet absorbance and mass spectroscopy. Antifungal activity against C albicans and A fumigatus was determined in a well plate assay. RESULTS: Pyocyanin was the major antifungal agent of P aeruginosa; 1-hydroxy-phenazine also possessed activity. Pyocyanin MICs for C albicans and A fumigatus were > 64 micrograms/ml. These phenazines were active against nine other yeast species pathogenic for man. Preliminary experiments also suggested possible inhibition of yeast mycelial transformation in C albicans by pyocyanin. CONCLUSIONS: There may be a role for pyocyanin and 1-hydroxyphenazine in the prevention of pulmonary candidiasis in patients colonised by P aeruginosa.